(untitled) (Innovaciones Educativas, 2025)
This qualitative hermeneutic study focused on evaluating the effectiveness of a training program designed for 10 faculty members from the Computer Engineering program at UNED. The main objective was to develop competencies in programming the humanoid robot NAO. The NAO robot was selected for its versatility and for the pressing need to modernize pedagogical practices in the field. Through a blended workshop (virtual and in-person), combining theoretical and practical materials, participating instructors acquired essential programming skills and learned to design innovative educational activities using the robot as a teaching tool. The study revealed unanimous acceptance (100%) among participants regarding the integration of NAO into their teaching practices. Teachers highlighted both the ease of implementing the robot and its relevance in enhancing educational quality. However, the need for more rigorous and periodic studies was emphasized to strengthen the reliability of the findings. This suggestion underscores the importance of continuous and systematic evaluation to consolidate outcomes. In conclusion, the training program had a positive impact on the development of teachers’ digital competencies. Participants acquired the ability to program and meaningfully integrate robotics into their teaching practices, significantly enriching students’ learning experiences. Nevertheless, the study also identified challenges, including infrastructure requirements, time constraints for hands-on practice, and the effective implementation of newly acquired skills.